\documentclass[a4paper,10pt]{article} \usepackage{myXsim} \usepackage{amsmath} \author{Benjamin Bertrand} \title{Information chiffrée 1 - Exercices} \date{Octobre 2021} \xsimsetup{ solution/print = false } \pagestyle{empty} \begin{document} \begin{exercise}[subtitle={Réductions}] Réduire les expressions suivantes \begin{multicols}{3} \begin{enumerate}[label={\Alph*=}] \item $7x + 1 + 7x + 8$ \item $3x - 6 + 4x - 2$ \item $- 4x^{2} - 6 - 6x^{2} + 6 + 6x + 8$ \item $- 1x + 3 - 8x + 1 - 9x - 2x$ \item $18x + 19 + 12x + 4x + 18$ \item $- 3x - 7 + 3x + 9$ \end{enumerate} \end{multicols} \end{exercise} \begin{solution} \begin{multicols}{3} \begin{flalign*} A =& 7x + 1 + 7x + 8\\ =& 7x + 1 + 7x + 8\\ =& 7x + 7x + 1 + 8\\ =& (7 + 7) \times x + 9\\ =& 14x + 9 \end{flalign*} \begin{flalign*} B =& 3x - 6 + 4x - 2\\ =& 3x - 6 + 4x - 2\\ =& 3x + 4x - 6 - 2\\ =& (3 + 4) \times x - 8\\ =& 7x - 8 \end{flalign*} \begin{flalign*} C =& - 4x^{2} - 6 - 6x^{2} + 6 + 6x + 8\\ =& - 4x^{2} - 6x^{2} - 6 + 14 + 6x\\ =& (- 4 - 6) \times x^{2} + 6x - 6 + 14\\ =& - 10x^{2} + 6x + 8 \end{flalign*} \begin{flalign*} D =& - 1x + 3 - 8x + 1 - 9x - 2x\\ =& - x + 3 + 1 - 8x + (- 9 - 2) \times x\\ =& (- 1 - 8) \times x + 4 - 11x\\ =& - 9x + 4 - 11x\\ =& - 9x - 11x + 4\\ =& (- 9 - 11) \times x + 4\\ =& - 20x + 4 \end{flalign*} \begin{flalign*} E =& 18x + 19 + 12x + 4x + 18\\ =& 18x + 19 + (12 + 4) \times x + 18\\ =& 18x + 19 + 18 + 16x\\ =& (18 + 16) \times x + 37\\ =& 34x + 37 \end{flalign*} \begin{flalign*} F =& - 3x - 7 + 3x + 9\\ =& - 3x - 7 + 3x + 9\\ =& - 3x + 3x - 7 + 9\\ =& (- 3 + 3) \times x + 2\\ =& 0x + 2\\ =& 2 \end{flalign*} \end{multicols} \end{solution} \begin{exercise}[subtitle={Simple développement}] Développer puis réduire les expressions suivantes \begin{multicols}{3} \begin{enumerate}[label={\Alph*=}] \item $10(x + 3)$ \item $- 3(- 5x - 6)$ \item $10(6x + 4)$ \item $5x(8x + 10)$ \item $- 10x(- 6x - 9) - 9$ \item $8x - 3x(- 6x - 7)$ \end{enumerate} \end{multicols} \end{exercise} \begin{solution} \begin{multicols}{3} \begin{flalign*} A =& 10(x + 3)\\ =& 10x + 10 \times 3\\ =& 10x + 30 \end{flalign*} \begin{flalign*} B =& - 3(- 5x - 6)\\ =& - 3 \times - 5x - 3(- 6)\\ =& - 3(- 5) \times x + 18\\ =& 15x + 18 \end{flalign*} \begin{flalign*} C =& 10(6x + 4)\\ =& 10 \times 6x + 10 \times 4\\ =& 10 \times 6 \times x + 40\\ =& 60x + 40 \end{flalign*} \begin{flalign*} D =& 5x(8x + 10)\\ =& 5x \times 8x + 5x \times 10\\ =& 5 \times 8 \times x^{1 + 1} + 10 \times 5 \times x\\ =& 40x^{2} + 50x \end{flalign*} \begin{flalign*} E =& - 10x(- 6x - 9) - 9\\ =& - 10x \times - 6x - 10x(- 9) - 9\\ =& - 10(- 6) \times x^{1 + 1} - 9(- 10) \times x - 9\\ =& 60x^{2} + 90x - 9 \end{flalign*} \begin{flalign*} F =& 8x - 3x(- 6x - 7)\\ =& 8x - 3x \times - 6x - 3x(- 7)\\ =& 8x - 3(- 6) \times x^{1 + 1} - 7(- 3) \times x\\ =& 8x + 21x + 18x^{2}\\ =& (8 + 21) \times x + 18x^{2}\\ =& 18x^{2} + 29x \end{flalign*} \end{multicols} \end{solution} \begin{exercise}[subtitle={Double développement}] Développer puis réduire les expressions suivantes \begin{multicols}{3} \begin{enumerate}[label={\Alph*=}] \item $(x + 4)(x - 4)$ \item $(6x + 2)(8x - 9)$ \item $(- 8x + 8)(- 2x + 2)$ \item $(6x + 9)(10x + 10)$ \item $(7x - 8)^{2}$ \item $(10x - 7)^{2}$ \end{enumerate} \end{multicols} \end{exercise} \begin{solution} \begin{multicols}{2} \begin{flalign*} A =& (x + 4)(x - 4)\\ =& x \times x + x(- 4) + 4x + 4(- 4)\\ =& x^{2} - 16 + (- 4 + 4) \times x\\ =& x^{2} - 16 \end{flalign*} \begin{flalign*} B =& (6x + 2)(8x - 9)\\ =& 6x \times 8x + 6x(- 9) + 2 \times 8x + 2(- 9)\\ =& 6 \times 8 \times x^{1 + 1} - 9 \times 6 \times x + 2 \times 8 \times x - 18\\ =& - 54x + 16x + 48x^{2} - 18\\ =& (- 54 + 16) \times x + 48x^{2} - 18\\ =& 48x^{2} - 38x - 18 \end{flalign*} \begin{flalign*} C =& (- 8x + 8)(- 2x + 2)\\ =& - 8x \times - 2x - 8x \times 2 + 8 \times - 2x + 8 \times 2\\ =& - 8(- 2) \times x^{1 + 1} + 2(- 8) \times x + 8(- 2) \times x + 16\\ =& - 16x - 16x + 16x^{2} + 16\\ =& (- 16 - 16) \times x + 16x^{2} + 16\\ =& 16x^{2} - 32x + 16 \end{flalign*} \begin{flalign*} D =& (6x + 9)(10x + 10)\\ =& 6x \times 10x + 6x \times 10 + 9 \times 10x + 9 \times 10\\ =& 6 \times 10 \times x^{1 + 1} + 10 \times 6 \times x + 9 \times 10 \times x + 90\\ =& 60x + 90x + 60x^{2} + 90\\ =& (60 + 90) \times x + 60x^{2} + 90\\ =& 60x^{2} + 150x + 90 \end{flalign*} \begin{flalign*} E =& (7x - 8)^{2}\\ =& (7x - 8)(7x - 8)\\ =& 7x \times 7x + 7x(- 8) - 8 \times 7x - 8(- 8)\\ =& 7 \times 7 \times x^{1 + 1} - 8 \times 7 \times x - 8 \times 7 \times x + 64\\ =& - 56x - 56x + 49x^{2} + 64\\ =& (- 56 - 56) \times x + 49x^{2} + 64\\ =& 49x^{2} - 112x + 64 \end{flalign*} \begin{flalign*} F =& (10x - 7)^{2}\\ =& (10x - 7)(10x - 7)\\ =& 10x \times 10x + 10x(- 7) - 7 \times 10x - 7(- 7)\\ =& 10 \times 10 \times x^{1 + 1} - 7 \times 10 \times x - 7 \times 10 \times x + 49\\ =& - 70x - 70x + 100x^{2} + 49\\ =& (- 70 - 70) \times x + 100x^{2} + 49\\ =& 100x^{2} - 140x + 49 \end{flalign*} \end{multicols} \end{solution} \begin{exercise}[subtitle={Double développement}] Développer puis réduire les expressions suivantes \begin{multicols}{3} \begin{enumerate}[label={\Alph*=}] \item $2x + \dfrac{- 8}{7} - 8x + \dfrac{- 5}{7}$ \item $8\left(- 4x + \dfrac{3}{5}\right)$ \item $\left(\dfrac{- 5}{- 4} x - 4\right)\left(3x + \dfrac{8}{10}\right)$ \end{enumerate} \end{multicols} \end{exercise} \begin{solution} \begin{multicols}{2} \begin{flalign*} A =& 2x + \dfrac{- 8}{7} - 8x + \dfrac{- 5}{7}\\ =& 2x + \dfrac{- 8}{7} + \dfrac{- 5}{7} - 8x\\ =& (2 - 8) \times x + \dfrac{- 8 - 5}{7}\\ =& - 6x + \dfrac{- 13}{7} \end{flalign*} \begin{flalign*} B =& 8(- 4x + \dfrac{3}{5})\\ =& 8 \times - 4x + 8 \times \dfrac{3}{5}\\ =& 8(- 4) \times x + \dfrac{8 \times 3}{5}\\ =& - 32x + \dfrac{24}{5} \end{flalign*} \begin{flalign*} C =& \left(\dfrac{- 5}{- 4} \times x - 4\right)\left(3x + \dfrac{8}{10}\right)\\ =& \dfrac{- 5}{- 4} \times x \times 3x + \dfrac{- 5}{- 4} \times x \times \dfrac{8}{10} - 4 \times 3x - 4 \times \dfrac{8}{10}\\ =& \dfrac{- 5}{- 4} \times 3 \times x^{1 + 1} + \dfrac{8}{10} \times \dfrac{- 5}{- 4} \times x - 4 \times 3 \times x + \dfrac{- 4 \times 8}{10}\\ =& \dfrac{- 5 \times 3}{- 4} \times x^{2} + \dfrac{8\left(- 5\right)}{10\left(- 4\right)} \times x - 12x + \dfrac{- 32}{10}\\ =& \dfrac{- 40}{- 40} \times x + \dfrac{- 15}{- 4} \times x^{2} - 12x + \dfrac{- 32}{10}\\ =& \dfrac{- 15}{- 4} \times x^{2} + \dfrac{- 40}{- 40} \times x - 12x + \dfrac{- 32}{10}\\ =& \dfrac{- 15}{- 4} \times x^{2} + \left(\dfrac{- 40}{- 40} - 12\right) \times x + \dfrac{- 32}{10}\\ =& \dfrac{- 15}{- 4} \times x^{2} + \dfrac{- 32}{10} + \left(\dfrac{- 40}{- 40} + \dfrac{- 12}{1}\right) \times x\\ =& \dfrac{- 15}{- 4} \times x^{2} + \dfrac{- 32}{10} + \left(\dfrac{- 40}{- 40} + \dfrac{- 12\left(- 40\right)}{1\left(- 40\right)}\right) \times x\\ =& \dfrac{- 15}{- 4} \times x^{2} + \dfrac{- 32}{10} + \left(\dfrac{- 40}{- 40} + \dfrac{480}{- 40}\right) \times x\\ =& \dfrac{- 15}{- 4} \times x^{2} + \dfrac{- 32}{10} + \dfrac{- 40 + 480}{- 40} \times x\\ =& \dfrac{- 15}{- 4} \times x^{2} + \dfrac{440}{- 40} \times x + \dfrac{- 32}{10} \end{flalign*} \end{multicols} \end{solution} \vfill \printexercise{exercise}{1,2,3,4} \vfill \newpage \printsolutionstype{exercise} \end{document}